Severe Valvular Aortic Stenosis and Homozygous Familial Hypercholesterolemia in a 8 Year Old Female Child - Case Report - Razzaque, S-K A; Islam, MS; Haque, A; Shariar, A; Alam, MJ; Harun, JIMA; Islam, F; Saha, SK; Hossain, MK (Cardiovascular Journal, 2011)
DOI: http://dx.doi.org/10.3329/cardio.v1i1.8208 Cardiovasc. j. 2008; 1(1) : 115-116